A method for preparing a tantalum carbide based on deep eutectic solvent
The method for preparing tantalum carbide using a deep eutectic solvent solves the problems of high temperature, high energy consumption, uneven mixing, and many impurities in the preparation of tantalum carbide. It achieves molecular-level uniform distribution of tantalum and carbon at low temperature and prepares high-purity nanoscale tantalum carbide powder.
Patent Information
- Application Number
- CN202611446330.2
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2026-09-17
- Publication Date
- 2026-11-06
AI Technical Summary
Existing methods for preparing tantalum carbide suffer from problems such as high reaction temperature, high energy consumption, uneven mixing, numerous impurities, and large particle size, making it difficult to achieve low-temperature carbonization, molecular-level uniform mixing, and the preparation of high-purity nanoscale products.
Using a deep eutectic solvent as the dissolution medium and carbon source, tantalum salts are uniformly dispersed through hydrogen bonds or weak coordination bonds to form a three-dimensional network structure composite gel. Heat treatment is performed at low temperature, and the amorphous carbon skeleton is used to restrict grain growth, thereby achieving a molecular-level uniform distribution of tantalum and carbon and the absence of Ta2C impurity phase formation.
This method achieves molecular-level uniform distribution of tantalum and carbon, reduces reaction temperature and energy consumption, and produces tantalum carbide powder with high purity and small particle size. It also avoids Ta2C and residual Ta2O5 impurities, simplifying subsequent purification processes.
Smart Images

Figure CN123041908A_ABST
Abstract
Description
Technical Field
[0001] This invention relates to the field of tantalum carbide technology, and more specifically to a method for preparing tantalum carbide based on a deep eutectic solvent. Background Technology
[0002] Tantalum carbide is a typical transition metal carbide, belonging to the face-centered cubic crystal system (NaCl type structure), and appears as a yellowish-brown to dark brown powder. It has a high melting point of 3880℃ and exhibits extremely high hardness (Mohs hardness 9-10, Vickers hardness approximately 2100 HV 0.05), excellent chemical stability, good electrical and thermal conductivity, and thermal shock resistance. Therefore, tantalum carbide is widely used in aerospace ultra-high temperature coatings, cemented carbide cutting tools, semiconductor diffusion barrier layers, and ultra-high temperature structural ceramics. However, its widespread application is still limited by factors such as poor ductility, brittleness, and high processing costs.
[0003] Currently, the main methods for preparing tantalum carbide include carbothermal reduction, chemical reaction, high-temperature molten salt method, chemical vapor deposition, and sol-gel method. Among these, carbothermal reduction is the most traditional and mainstream process, which involves mixing tantalum oxide (such as Ta₂O₅) with carbon (carbon black, graphite, etc.) at high temperatures and then carrying out a carbonization reaction. However, this method has many drawbacks: extremely high reaction temperatures (typically 1500-2200℃), huge energy consumption, and slow reaction rates; poor solid-phase mixing uniformity, with uneven mixing of tantalum oxide powder and carbon black or graphite powder, easily leading to the formation of Ta₂C impurity phases or residual free carbon; and the product powder is prone to agglomeration and has a large particle size. Chemical reaction (solid-phase method) is a common solid-phase preparation process, in which tantalum and carbon directly react chemically under certain conditions to produce tantalum carbide. This method also faces the problems of high reaction temperatures and difficulty in controlling product particle size. The high-temperature molten salt method uses molten salt (such as NaCl-NaF) as the reaction medium, which can reduce the reaction temperature to a certain extent. However, this method suffers from molten salt residue issues, requiring complex purification processes to remove residual halides in the product; furthermore, the molten salt may participate in the formation of intermediate products (such as NaTaO3) during the reaction, increasing the complexity of the reaction pathway. Chemical vapor deposition (CVD) deposits TaC coatings on the substrate surface via a gaseous precursor reaction. This method is suitable for thin film and coating preparation, but it is difficult to achieve large-scale powder production; it involves large equipment investment, complex processes, and high production costs. The sol-gel method uses organic tantalum or tantalum inorganic salt as a precursor, reacting with a solvent to form a sol, which is then gelled, dried, and sintered to obtain tantalum carbide. However, this method has drawbacks, including a long cycle time, the need to add other additives, and subsequent calcination affecting the quality of tantalum carbide.
[0004] Therefore, developing a novel tantalum carbide preparation method that can simultaneously achieve low-temperature carbonization, molecular-level uniform mixing, short-process efficient preparation, and high-purity nanoscale products has become a direction that urgently needs to be broken through in this field. Summary of the Invention
[0005] The purpose of this invention is to overcome the shortcomings of existing sugar gel and solid-phase carbothermal reduction processes, such as uneven mixing, high reaction temperature, many impurities, long cycle, and large powder particle size, and to achieve uniform dispersion of tantalum source at the molecular level and low-temperature carbonization to prepare tantalum carbide with fine grains and high purity.
[0006] To achieve the above-mentioned technical objectives, this invention provides a method for preparing tantalum carbide based on a deep eutectic solvent, comprising: The tantalum salt was dissolved in a deep eutectic solvent to obtain the precursor solution; The precursor solution was subjected to a first heat treatment to obtain a composite gel. The composite gel was subjected to a second heat treatment to obtain tantalum carbide.
[0007] Furthermore, the mass concentration of tantalum salt in the precursor solution is 12%-18%.
[0008] Furthermore, the deep eutectic solvent is composed of hydrogen bond acceptors and hydrogen bond donors in a molar ratio of 1.8-2.2:1.
[0009] Furthermore, the hydrogen bond acceptors include choline chloride, choline bromide, choline iodide, and N-hydroxylamine. benzyl 2 Hydroxyl N,N Dimethylethanolammonium chloride, N Ethyl 2 hydroxyl N,N At least one of dimethyl ethanol ammonium chloride; The hydrogen bond donor includes at least one of glucose, ethylene glycol, p-toluenesulfonic acid, formic acid, acetic acid, oxalic acid, malonic acid, succinic acid, glutaric acid, glycerol, and citric acid.
[0010] Furthermore, the dissolution is carried out at a temperature of 80-100°C.
[0011] Furthermore, the first heat treatment is carried out in a protective atmosphere at a temperature of 250-350°C for 1.5-2.5 hours.
[0012] Furthermore, the second heat treatment is carried out in a protective atmosphere, with a heating rate of 3-8℃ / min to 1200-1300℃ and held for 1-2 hours.
[0013] Furthermore, the tantalum salt is a tantalum halide salt.
[0014] Furthermore, when dissolving tantalum salts in a deep eutectic solvent, the water and oxygen content in the environment is controlled to be <1 ppm.
[0015] The present invention also provides tantalum carbide, which is obtained by the above preparation method.
[0016] Compared with the prior art, the beneficial effects of the present invention include: The present invention provides a method for preparing tantalum carbide based on a deep eutectic solvent. The deep eutectic solvent system is used as a carbon source and can effectively dissolve tantalum salt. The dissolution of tantalum salt results in a uniform distribution of tantalum and carbon at the molecular scale. The resulting composite gel undergoes a more complete reduction reaction in the subsequent process. The prepared tantalum carbide is free of Ta2C and residual Ta2O5 impurities. At the same time, the present invention does not require the addition of additional organic reagents, reducing the introduction of impurity sources and improving the purity of the tantalum carbide product.
[0017] The above description is only an overview of the technical solution of this application. In order to better understand the technical means of this application and to implement it in accordance with the contents of the specification, and to make the above and other objects, features and advantages of this application more obvious and understandable, the following are specific embodiments of this application. Attached Figure Description
[0018] To more clearly illustrate the technical solutions of this application, the accompanying drawings used in this application will be briefly described below. Obviously, the drawings described below are merely some embodiments of this application. For those skilled in the art, other drawings can be obtained from these drawings without any creative effort.
[0019] Figure 1 A flowchart of the tantalum carbide preparation method based on deep eutectic solvent of the present invention is shown. Detailed Implementation
[0020] To make the objectives, technical solutions, and advantages of this invention clearer, the invention will be further described in detail below with reference to the accompanying drawings and embodiments. It should be understood that the specific embodiments described herein are merely illustrative and not intended to limit the invention.
[0021] Unless otherwise defined, all technical and scientific terms used herein have the same meaning as commonly understood by one of ordinary skill in the art to which this invention pertains; the terminology used herein is for the purpose of describing particular embodiments only and is not intended to limit the invention; the terms “comprising” and “having”, and any variations thereof, in the specification, claims, and foregoing description of the invention, are intended to cover non-exclusive inclusion.
[0022] In this document, the term "embodiment" means that a particular feature, structure, or characteristic described in connection with an embodiment may be included in at least one embodiment of the invention. The appearance of this phrase in various places throughout the specification does not necessarily refer to the same embodiment, nor is it a separate or alternative embodiment mutually exclusive with other embodiments. It will be explicitly and implicitly understood by those skilled in the art that the embodiments described herein can be combined with other embodiments.
[0023] Current tantalum carbide preparation technologies share the following common bottlenecks: 1. High reaction temperature and high energy consumption. Whether it's carbothermal reduction or solid-state synthesis, traditional processes generally require temperatures above 1500℃ or even higher. High temperatures not only lead to enormous energy consumption but also cause severe grain coarsening, making it difficult to obtain nanoscale powders. Literature reports that TaC ceramic powders prepared by solid-state reactions and high-temperature self-propagating synthesis generally suffer from problems such as large particle size, uneven elemental distribution, and low purity.
[0024] 2. Poor uniformity of mixing between tantalum and carbon sources. In solid-phase mixing processes, Ta2O5 powder and carbon sources can only achieve physical mixing at the micrometer scale, making it difficult to achieve uniform dispersion at the molecular level. Even with liquid-phase assisted mixing, local segregation problems still exist, affecting the phase purity and consistency of the product.
[0025] 3. The product has a large particle size and low purity. High-temperature reactions inevitably lead to grain growth, and commercial TaC powders generally suffer from low purity and large particle size, resulting in poor sintering performance. The size, morphology, distribution, agglomeration degree, and chemical purity of the powder particles will have a significant impact on subsequent molding and sintering.
[0026] 4. Difficulty in introducing and purifying impurities. Some processes (such as molten salt method and sol-gel method) inevitably introduce foreign impurities (halides, organic residues, etc.), making subsequent purification steps complex. Substoichiometric TaC 1-x Impurity phases of the same type are difficult to remove by conventional washing steps because they are almost insoluble in water or acid.
[0027] Therefore, this invention is proposed.
[0028] A method for preparing tantalum carbide based on a deep eutectic solvent, comprising, The tantalum salt was dissolved in a deep eutectic solvent to obtain the precursor solution; The precursor solution was subjected to a first heat treatment to obtain a composite gel. The composite gel was subjected to a second heat treatment to obtain tantalum carbide.
[0029] In some preferred embodiments, the mass concentration of tantalum salt in the precursor solution is 12%-18%.
[0030] In some preferred embodiments, the deep eutectic solvent consists of hydrogen bond acceptors and hydrogen bond donors in a molar ratio of 1.8-2.2:1.
[0031] In this invention, the deep eutectic solvent is not merely an inert reaction medium, but a multifunctional system integrating a molecular-level solvent, an in-situ carbon source, and a nano-confined template: (1) Coordination dissolution mechanism of tantalum salt This invention employs hydrogen bond acceptors containing quaternary ammonium groups and hydrogen bond donors containing hydroxyl, sulfonic acid, and carboxyl groups. After mixing, the hydrogen bond acceptors and hydrogen bond donors form a strong hydrogen bond network, which anchors tantalum through hydrogen bonds or weak coordination bonds, enabling tantalum to achieve a truly "molecular / ionic" uniform dispersion in the liquid phase.
[0032] (2) In-situ carbon fixation and skeleton anchoring mechanism During the first heat treatment, small molecule volatiles (water, HCl, etc.) in the system are removed, and the supramolecular network of the eutectic solvent collapses into an amorphous carbon skeleton. Quaternary ammonium groups undergo cross-linking reactions with active carbon fragments generated from the pyrolysis of hydrogen bond donors, forming a Ta-C composite dry gel with a three-dimensional network structure. In conventional direct pyrolysis of glucose, carbon elements easily escape in the form of CO, CO2, and tar. The "in-situ carbon cage" physical barrier formed during pyrolysis in this invention effectively inhibits the volatilization of small molecule carbon oxides.
[0033] (3) Spatial confinement and kinetic suppression mechanism of grain refinement During the second heat treatment, the three-dimensional amorphous carbon framework formed in the earlier stage acts as a physical isolation layer. TaC crystal nuclei grow in situ within the carbon matrix, and the nanopores of the carbon framework restrict the migration and merging of grains, thus ensuring the product grain size. Because Ta and C are premixed at the molecular scale, the reaction nucleation sites during carbonization are extremely dense and uniformly distributed, avoiding the formation of Ta2C intermediate phase in local tantalum-rich regions and the residual free carbon in local carbon-rich regions. This achieves the direct formation of single-phase TaC, eliminating the need for subsequent acid washing and impurity removal processes.
[0034] In some preferred embodiments, the hydrogen bond acceptor includes choline chloride, choline bromide, choline iodide, and N-methyl-2-ethylhexyl chloride. benzyl 2 Hydroxyl N,N Dimethylethanolammonium chloride, N Ethyl 2 hydroxyl N,N At least one of dimethyl ethanol ammonium chloride; The hydrogen bond donor includes at least one of glucose, ethylene glycol, p-toluenesulfonic acid, formic acid, acetic acid, oxalic acid, malonic acid, succinic acid, glutaric acid, glycerol, and citric acid.
[0035] In some preferred embodiments, the dissolution is carried out at a temperature of 80-100°C.
[0036] In some preferred embodiments, the first heat treatment is carried out under a protective atmosphere at a temperature of 250-350°C for 1.5-2.5 hours. Pre-carbonization at a lower temperature removes small-molecule volatiles from the system, and the supramolecular network of the eutectic solvent collapses into an amorphous carbon skeleton. Quaternary ammonium groups undergo cross-linking reactions with active carbon fragments generated from the pyrolysis of hydrogen bond donors, forming a Ta-C composite dry gel with a three-dimensional network structure.
[0037] In some preferred embodiments, the second heat treatment is carried out under a protective atmosphere, with a heating rate of 3-8°C / min to 1200-1300°C and a holding time of 1-2 hours. The three-dimensional network structure of the Ta-C composite dry gel, compared to carbon black, sucrose, and glucose pyrolysis carbon, exhibits more disordered defect structures and a higher specific surface area. This highly active amorphous carbon significantly reduces the apparent activation energy of the carbothermic reduction reaction, thereby lowering the carbonization reduction temperature.
[0038] In some preferred embodiments, the tantalum salt is a tantalum halide salt.
[0039] In some preferred embodiments, when dissolving tantalum salts in a deep eutectic solvent, the water and oxygen content in the environment is controlled to be <1 ppm. Dissolving in a low water and oxygen content environment can prevent the hydrolysis of tantalum salts.
[0040] The present invention will be further described in detail below through specific embodiments. It should be noted that the embodiments described below are exemplary and are only used to explain this application, and should not be construed as limiting this application. Where specific techniques or conditions are not specified in the embodiments, they shall be performed in accordance with the techniques or conditions described in the literature in this field or in accordance with the product instructions. Reagents or instruments used that do not specify the manufacturer are all conventional products that can be obtained commercially.
[0041] Example 1 like Figure 1 As shown, a method for preparing tantalum carbide based on a deep eutectic solvent includes the following steps: S1, Preparation of deep eutectic solvent Choline chloride and glucose monohydrate were mixed at a molar ratio of 1.8:1 and stirred at 85°C until completely transparent to obtain a deep eutectic solvent.
[0042] S2, Preparation of precursor solution In a glove box isolated from air and with a water and oxygen content of <1ppm, tantalum pentachloride was added to a deep eutectic solvent at a mass concentration of 15%, and stirred at 80°C until completely dissolved to obtain a clear precursor solution.
[0043] S3, Pre-carbonized The precursor solution was kept at 300℃ for 2.0 h under a nitrogen atmosphere to remove small molecule volatiles, resulting in a composite gel.
[0044] S4, Low-temperature carbonization The composite gel was heated to 1250℃ for 1.5h at a heating rate of 5℃ / min under an argon atmosphere, and then naturally cooled, ground and sieved to obtain tantalum carbide powder.
[0045] Example 2 A method for preparing tantalum carbide based on a deep eutectic solvent includes the following steps: S1, Preparation of deep eutectic solvent Choline chloride and glucose monohydrate were mixed at a molar ratio of 2.0:1 and stirred at 85°C until completely transparent to obtain a deep eutectic solvent.
[0046] S2, Preparation of precursor solution In a glove box isolated from air and with a water and oxygen content of <1ppm, tantalum pentachloride was added to a deep eutectic solvent at a mass concentration of 15%, and stirred at 80°C until completely dissolved to obtain a clear precursor solution.
[0047] S3, Pre-carbonized The precursor solution was kept at 300℃ for 2.0 h under a nitrogen atmosphere to remove small molecule volatiles, resulting in a composite gel.
[0048] S4, Low-temperature carbonization The composite gel was heated to 1250℃ for 1.5h at a heating rate of 5℃ / min under an argon atmosphere, and then naturally cooled, ground and sieved to obtain tantalum carbide powder.
[0049] Example 3 A method for preparing tantalum carbide based on a deep eutectic solvent includes the following steps: S1, Preparation of deep eutectic solvent Choline chloride and glucose monohydrate were mixed at a molar ratio of 2.2:1 and stirred at 85°C until completely transparent to obtain a deep eutectic solvent.
[0050] S2, Preparation of precursor solution In a glove box isolated from air and with a water and oxygen content of <1ppm, tantalum pentachloride was added to a deep eutectic solvent at a mass concentration of 15%, and stirred at 80°C until completely dissolved to obtain a clear precursor solution.
[0051] S3, Pre-carbonized The precursor solution was kept at 300℃ for 2.0 h under a nitrogen atmosphere to remove small molecule volatiles, resulting in a composite gel.
[0052] S4, Low-temperature carbonization The composite gel was heated to 1250℃ for 1.5h at a heating rate of 5℃ / min under an argon atmosphere, and then naturally cooled, ground and sieved to obtain tantalum carbide powder.
[0053] Example 4 A method for preparing tantalum carbide based on a deep eutectic solvent includes the following steps: S1, Preparation of deep eutectic solvent Choline bromide and ethylene glycol were mixed at a molar ratio of 2.0:1 and stirred at 85°C until completely transparent to obtain a deep eutectic solvent.
[0054] S2, Preparation of precursor solution In a glove box isolated from air and with a water and oxygen content of <1ppm, tantalum pentachloride was added to a deep eutectic solvent at a mass concentration of 15%, and stirred at 80°C until completely dissolved to obtain a clear precursor solution.
[0055] S3, Pre-carbonized The precursor solution was kept at 300℃ for 2.0 h under a nitrogen atmosphere to remove small molecule volatiles, resulting in a composite gel.
[0056] S4, Low-temperature carbonization The composite gel was heated to 1250℃ for 1.5h at a heating rate of 5℃ / min under an argon atmosphere, and then naturally cooled, ground and sieved to obtain tantalum carbide powder.
[0057] Example 5 A method for preparing tantalum carbide based on a deep eutectic solvent includes the following steps: S1, Preparation of deep eutectic solvent N Ethyl 2 hydroxyl N,N Dimethyl ethanol ammonium chloride and oxalic acid are mixed at a molar ratio of 2.0:1 and stirred at 85°C until completely transparent to obtain a deep eutectic solvent.
[0058] S2, Preparation of precursor solution In a glove box isolated from air and with a water and oxygen content of <1ppm, tantalum pentachloride was added to a deep eutectic solvent at a mass concentration of 15%, and stirred at 80°C until completely dissolved to obtain a clear precursor solution.
[0059] S3, Pre-carbonized The precursor solution was kept at 300℃ for 2.0 h under a nitrogen atmosphere to remove small molecule volatiles, resulting in a composite gel.
[0060] S4, Low-temperature carbonization The composite gel was heated to 1250℃ for 1.5h at a heating rate of 5℃ / min under an argon atmosphere, and then naturally cooled, ground and sieved to obtain tantalum carbide powder.
[0061] Example 6 A method for preparing tantalum carbide based on a deep eutectic solvent includes the following steps: S1, Preparation of deep eutectic solvent N benzyl 2 hydroxyl N,N Dimethyl ethanol ammonium chloride and p-toluenesulfonic acid were mixed at a molar ratio of 2.0:1 and stirred at 85°C until completely transparent to obtain a deep eutectic solvent.
[0062] S2, Preparation of precursor solution In a glove box isolated from air and with a water and oxygen content of <1ppm, tantalum pentachloride was added to a deep eutectic solvent at a mass concentration of 15%, and stirred at 80°C until completely dissolved to obtain a clear precursor solution.
[0063] S3, Pre-carbonized The precursor solution was kept at 300℃ for 2.0 h under a nitrogen atmosphere to remove small molecule volatiles, resulting in a composite gel.
[0064] S4, Low-temperature carbonization The composite gel was heated to 1250℃ for 1.5h at a heating rate of 5℃ / min under an argon atmosphere, and then naturally cooled, ground and sieved to obtain tantalum carbide powder.
[0065] Comparative Example 1 A method for preparing tantalum carbide includes the following steps: 1. In a glove box isolated from air and with an oxygen content of <1 ppm, tantalum pentachloride and glucose monohydrate were dissolved in anhydrous ethanol and stirred at 50°C until completely dissolved to obtain a clear precursor solution. The mass concentration of tantalum pentachloride in the precursor solution was 15%, and the molar ratio of tantalum pentachloride to glucose monohydrate was 1:1.8. This comparative example does not use a deep eutectic solvent; only ordinary ethanol is used, and glucose serves as both a carbon source and a reducing agent.
[0066] 2. The precursor solution was kept at 300℃ for 2.0h under a nitrogen atmosphere to remove small molecule volatiles and obtain a composite gel.
[0067] 3. The composite gel was heated to 1450℃ at a heating rate of 5℃ / min under an argon atmosphere and held for 1.5h. After natural cooling, it was ground and sieved to obtain tantalum carbide powder.
[0068] The particle size of the tantalum carbide prepared in the examples and comparative examples was measured using a laser particle size analyzer and transmission electron microscopy (TEM), and the results are shown in Table 1.
[0069] Table 1
[0070] As can be seen from the test results in Table 1, the tantalum carbide prepared by the eutectic solvent-based method provided in Examples 1-6 of this invention has smaller particle size and more uniform particle size distribution. This is due to: the present invention uses a eutectic solvent as a dispersion medium and carbon source, anchoring tantalum through hydrogen bonds or weak coordination bonds during dissolution, so that tantalum achieves a truly "molecular / ionic" uniform dispersion state in the liquid phase; during low-temperature carbonization, small molecule volatiles (water, HCl, etc.) in the system are removed, and the supramolecular network of the eutectic solvent collapses and transforms into an amorphous carbon skeleton; the quaternary ammonium groups undergo cross-linking reaction with the active carbon fragments generated by the pyrolysis of hydrogen bond donors to form a Ta-C composite dry gel with a three-dimensional network structure; in the subsequent high-temperature carbonization reduction, the three-dimensional amorphous carbon skeleton formed in the early stage acts as a physical isolation layer. TaC crystal nuclei grow in situ inside the carbon matrix, and the nanopores of the carbon skeleton restrict the migration and merging of grains, thereby ensuring the product grain size. Comparative Example 1 uses ethanol as the liquid medium and glucose as the carbon source, and also undergoes gelation. In heat treatment processes, due to the absence of a deep eutectic solvent hydrogen bond supramolecular network, tantalum ions cannot achieve molecular / ionic level anchoring and dispersion. They rely solely on ordinary liquid phase mixing, resulting in larger particle sizes and greater randomness in their distribution.
[0071] In summary, the tantalum carbide preparation method based on eutectic solvent provided by this invention uses a eutectic solvent system as a carbon source and can effectively dissolve tantalum salts. The dissolution of tantalum salts results in a uniform distribution of tantalum and carbon at the molecular scale, leading to a more complete reduction reaction in the resulting composite gel. The prepared tantalum carbide is free of Ta2C and residual Ta2O5 impurities. Furthermore, this invention eliminates the need for additional organic reagents, reducing the introduction of impurity sources and improving the purity of the tantalum carbide product.
[0072] The specific embodiments of the present invention described above do not constitute a limitation on the scope of protection of the present invention. Any other corresponding changes and modifications made in accordance with the technical concept of the present invention should be included within the scope of protection of the claims of the present invention.
Claims
1. A method for preparing tantalum carbide based on a deep eutectic solvent, characterized in that, include, The tantalum salt was dissolved in a deep eutectic solvent to obtain the precursor solution; The precursor solution was subjected to a first heat treatment to obtain a composite gel. The composite gel was subjected to a second heat treatment to obtain tantalum carbide.
2. The method for preparing tantalum carbide based on a deep eutectic solvent according to claim 1, characterized in that, The mass concentration of tantalum salt in the precursor solution is 12%-18%.
3. The method for preparing tantalum carbide based on a deep eutectic solvent according to claim 1, characterized in that, The deep eutectic solvent is composed of hydrogen bond acceptors and hydrogen bond donors in a molar ratio of 1.8-2.2:
1.
4. The method for preparing tantalum carbide based on a deep eutectic solvent according to claim 3, characterized in that, The hydrogen bond acceptors include choline chloride, choline bromide, choline iodide, and N. benzyl 2 Hydroxyl N,N Dimethylethanolammonium chloride, N Ethyl 2 hydroxyl N,N At least one of dimethyl ethanol ammonium chloride; The hydrogen bond donor includes at least one of glucose, ethylene glycol, p-toluenesulfonic acid, formic acid, acetic acid, oxalic acid, malonic acid, succinic acid, glutaric acid, glycerol, and citric acid.
5. The method for preparing tantalum carbide based on a deep eutectic solvent according to claim 1, characterized in that, The dissolution is carried out at a temperature of 80-100℃.
6. The method for preparing tantalum carbide based on a deep eutectic solvent according to claim 1, characterized in that, The first heat treatment is carried out in a protective atmosphere at a temperature of 250-350℃ for 1.5-2.5 hours.
7. The method for preparing tantalum carbide based on a deep eutectic solvent according to claim 1, characterized in that, The second heat treatment is carried out in a protective atmosphere, with a heating rate of 3-8℃ / min to 1200-1300℃ and held for 1-2 hours.
8. The method for preparing tantalum carbide based on a deep eutectic solvent according to claim 1, characterized in that, The tantalum salt is a halide tantalum salt.
9. The method for preparing tantalum carbide based on a deep eutectic solvent according to any one of claims 1-8, characterized in that, When dissolving tantalum salts in a deep eutectic solvent, the water and oxygen content in the environment should be controlled to be less than 1 ppm.
10. A tantalum carbide, characterized in that, It is obtained by the preparation method according to any one of claims 1-9.
